Genomewide association study of immune traits in chicken F2 resource population. (7th February 2016) - Sun, Y.; Li, Q.; Hu, Y.; Sun, Y.; Liu, R.; Zheng, M.; Wen, J.; Li, P.; Liu, L.; Zhao, G.
Summary: Immune traits play pivotal roles in animal immune capacity development and disease resistance. Single nucleotide polymorphisms (SNPs) are common forms of genetic variations among individuals, which are thought to account for the majority of inherited phenotypic variations. In this study, we performed genomewide association, using the Illumina 60K SNP BeadChip studies to detect molecular markers and candidate genes associated with immune traits in an F2 population. Sixteen immune traits were measured. We identified 85 significant SNPs (p   <   2.98 × 10 −6 ) with 5% as the genomewide significance threshold, 380 SNPs of suggestive significance (p   <   5.96 × 10 −5 ) from simple model (general linear model, GLM) and 15 SNPs of suggestive significance (p   <   5.96 × 10 −5 ) from the compressed mixed linear model (MLM), which were also found in GLM (six significant SNPs and seven suggestive SNPs). Three significant SNPs (GGaluGA151406, Gga_rs14554319 and Gga_rs13593979) and candidate genes ( LYRM4 and KTN1 ) were found to be associated with avian influenza antibody titres, and the first two SNPs are from the results of two‐model analysis. For the immune organs, through the analysis of GLM, 19 SNPs were found to be significantly associated with the thymus weight, 61 SNPs were significantly associated with the bursa of Fabricius weight, six of which were located within a 34‐Mb region (125 846 474–159 649 698 bp) on chicken chromosome 1 (GGA1). A candidate region relevant to haematological traits from GLM was found in GGA4 and 9 loci were located on it. Three loci (GGaluGA348521, Gga_rs16098446 and GGaluGA348518) within 179 kb (16 286 868–16 466 134 bp) on GGAZ from GLM provided evidence that this genomic segment may be relevant to red blood cell volume distribution width (RDW). Our study provides a list of significant SNPs and candidate genes that will be valuable information for unveiling the underlying molecular mechanism of immune regulation.